Ambiente-Forma-Opera (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
The work of Michelangelo Lupone and CRM is presented and commented in the contest of those music researches that practices important multimedia components, in order to speak about the creative approach of the contemporary composers.Therefore, a wider vision of the concept of musical composition arises, which introduces new media for the processing of sound matter, for its production and communication, with an important spatial component.The space as a musical parameter introduces some basic concepts of Michelangelo Lupone’s compositional work, here illustrated with the works “Vita Segreta della materia”. “Music on artist paper” made with Gunther Uecker; “Volumi adattivi” with Licia Galizia; “Sorgenti Nascoste” with Mimmo Palladino.